The alpha-herpesviruses: molecular pathfinders in nervous system circuits - Ekstrand, Mats I. (2008)
Several neuroinvasive viruses can be used to study the mammalian nervous system. In particular, infection by pseudorabies virus (PRV), an α-herpesvirus with broad host range, reveals chains of functionally connected neurons in the nervous systems of a variety of mammals. The specificity of PRV trans-neuronal spread has been established in several systems. One attenuated strain, PRV-Bartha, causes a reduced inflammatory response and also spreads only from infected post- to pre-synaptic neurons. We review the basics of PRV tracing and then discuss new developments and novel approaches that have enabled a more detailed understanding of the architecture of the nervous system. As questions and techniques evolve in the field of neuroscience, advances in PRV tracing will certainly follow.